2005
DOI: 10.1167/iovs.05-0241
|View full text |Cite
|
Sign up to set email alerts
|

Topical Combination of NGF and DHA Increases Rabbit Corneal Nerve Regeneration after Photorefractive Keratectomy

Abstract: NGF plus DHA treatment after PRK in rabbits is associated with increased corneal nerve surface area, increased epithelial proliferation, and decreased rose bengal staining compared with NGF, DHA, or vehicle control alone. The combination of NGF plus DHA yields faster nerve recovery after PRK and may have therapeutic usefulness in the treatment of post-PRK dry eye and other neurotrophic keratopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 26 publications
3
64
0
Order By: Relevance
“…Neurotrophins are survival signals, in addition to being modulators of neurite branching, synaptogenesis, and synaptic plasticity (33,34). In this regard, nerve growth factor and DHA activate nerve regeneration after experimental cornea injury (35). Thus, the ability of neurotrophins to promote cell survival through NPD1 in the RPE cell, as described here, is also highly relevant to the response of the nervous system to injury and neurodegeneration.…”
Section: Discussionmentioning
confidence: 76%
“…Neurotrophins are survival signals, in addition to being modulators of neurite branching, synaptogenesis, and synaptic plasticity (33,34). In this regard, nerve growth factor and DHA activate nerve regeneration after experimental cornea injury (35). Thus, the ability of neurotrophins to promote cell survival through NPD1 in the RPE cell, as described here, is also highly relevant to the response of the nervous system to injury and neurodegeneration.…”
Section: Discussionmentioning
confidence: 76%
“…6 Also, animal studies have shown that NGF increases corneal cell proliferation in rabbits and dogs. 10,11 In the present study, we used hens as a better model to reproduce in vivo human corneal wound healing. [27][28][29][30][31][32][33][34][35][36] In addition, we tested the in vitro effects of NGF using Telomerase-immortalized HCLEs in contrast to previous works concentrated on the effect of NGF on corneal fibroblasts and conjunctiva epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical experience has shown that topical administration of NGF improves epithelial healing in patients with neurotrophic corneal ulceration [2][3][4][5] or after cataract surgery 6 and is also used to treat inflammation. 7,8 Animal models have also shown NGF benefits in corneal wound healing and nerve regeneration [9][10][11] ; however, detailed mechanisms by which NGF elicits its effect on the corneal surface remains unknown.…”
mentioning
confidence: 99%
“…Topical administration of these dietary compounds and their derivatives has also been investigated in animal models but this is not the subject of this review (Cortina et al, 2010;Esquenazi et al, 2005;Li et al, 2010;Rashid et al, 2008).…”
Section: Micronutrient Supplementation/dietary Nutraceuticalsmentioning
confidence: 99%